Polyomavirus Hominis 1(BK virus) Infection in Prostatic Tissues: Cancer versus Hyperplasia - Taghavi, Afsoon; Mohammadi-Torbati, Peyman; Kashi, Amir Hossein; Rezaee, Hanieh; Vaezjalali, Maryam (Urology Journal, 2015)
Purpose: Polyoma virus hominis 1, better known as BK virus (BKV) infection might be a predisposing factor for prostate cancer (PCa). The aim of this study was to compare the frequency of BK virus infection in pathological specimens of patients with PCa compared to patients with benign prostatic hyperplasia. Materials and Methods: From July 2011 to June 2012, paraffin-embedded tissue blocks of patients with PCa (60 specimens) and also with benign prostatic hyperplasia (60 specimens) were investigated. After DNA purification, existence of virus nucleic acid was assessed by polymerase chain reaction. Results: Viral DNA was identified in 9 patients (15%) with BPH and 17 patients (28%) with PCa (P =.076). In patients with PCa, viral DNA was observed more often in those with lower total Gleason scores (P = .045). Conclusion: The frequency of BK virus infection in PCa patients was higher than BPH patients. BK virus was more often observed in patients with lower Gleason scores. Less detection of BK virus DNA in overt cancer may prove the activity of the virus which paves the way for tumorigenic transformation at early stages of PCa.